2019
DOI: 10.2147/ott.s214319
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification Of Actionable Genetic Targets In Primary Cardiac Sarcomas</p>

Abstract: Background: Primary cardiac tumors are extremely rare; most are myxomas with a benign prognosis. However, primary sarcomas are highly aggressive and treatment options are limited. Radical surgery is often not feasible and conventional therapies provide only modest results. Due to the rare nature of primary cardiac tumors, there are no proper randomized studies to guide treatment. Their complexity requires alternative approaches in order to improve treatment efficacy. Methods: We isolated DNA from 5 primary car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Primary malignant HT are rare both in human and veterinary medicine. As a result, even in human medicine large-scale epidemiological studies on their occurrence or randomized control trials and meta-analyses on their treatment are lacking [ 32 ]. Moreover, cytological assessment of sarcomas can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Primary malignant HT are rare both in human and veterinary medicine. As a result, even in human medicine large-scale epidemiological studies on their occurrence or randomized control trials and meta-analyses on their treatment are lacking [ 32 ]. Moreover, cytological assessment of sarcomas can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the classification of UHGPC-SRCSs requires immunohistochemistry, and vimentin expression is considered reliable for this type of pSTS-h [8], as well as αsmooth muscle actin and cytokeratins [8]. In addition, chromosomal defects of AKT2 and RUNX2, mutation of PDGFRB, and a higher number of chromosomal aberrations have been described in these rare variants of SRCs [26].…”
Section: Undifferentiated High-grade Pleomorphic Sarcomamentioning
confidence: 99%
“…Immune checkpoint inhibitor (ICI)-based immunotherapy has shown promising efficacy in various malignancies ( 7 9 ). Evidence regarding ICI efficacy in RMS remains scarce ( 10 ). A multicenter phase 2 clinical trial showed that ICIs exhibited promising efficacy and an acceptable safety profile in advanced STS ( 11 ).…”
Section: Introductionmentioning
confidence: 99%